How Do American Bilinguals Make a Request in Indonesian and English? - Husein, Imelda Wahyuni; Syaifullah, Aceng Ruhendi; Kurniawan, Eri (Universitas Negeri Semarang, 2024)
Abstract Being able to speak a foreign language fluently is not enough in cross-cultural communication. In order to avoid miscommunication, the speaker needs to have the target language culture knowledge. Several utterances can be found rude by some cultures, while some culture might find it common. This could happen due to the differences of cultures and value. In small talk such as making a request, different culture has their own strategy, and some culture might find it rude when the speaker do not share the same the value and culture. This study aims to analyze American bilinguals in making a request in Indonesian and English. The data were collected based on DCT request scenarios and observation. There were five American participants who were involved in this study. The findings showed that American participants tended to be indirect when they made requests in English even though some of them were direct and they changed into direct strategies when they made a request in Indonesian. This study also reveals that in terms of making a request, Americans are more indirect when it comes to making a request. Therefore, it is suggested that having intercultural knowledge is important in learning a language in order to avoid misunderstanding.